The selection of preferred textbook based on the dominance method / Harliza Mohd Hanif ... [et al.] - Mohd Hanif, Harliza; Mohamad, Daud; Sulaiman, Nor Hashimah; Batcha, Siti Rahimah (Universiti Teknologi MARA Press (Penerbit UiTM), 2024)
Calculus is a mathematics subject normally taught at the tertiary level. Many calculus textbooks with different approaches and styles have been published to cater to the needs of students. The selection of calculus textbooks is essential as it can help teachers and students to optimize their usage. Textbook selection problem is one type of multiple-criteria decision making problem where the selection is based on several criteria. Thus, ranking fuzzy numbers based on the area dominance method ranks the calculus textbook.